The Development of Procedural Text Learning Module with an E-Learning-Based Flipped Classroom Model: - Syaifullah Syaifullah; Wenny Noorahim (Raja Zulkarnain Education Foundation, 2025)
This study aims to: 1) analyze the needs of procedural text writing skills of grade XI students at SMAN 7 Banjarmasin using the Flipped Classroom learning model based on e-learning; 2) develop a procedural text writing learning module that suits students' needs; and 3) test the feasibility of the module based on expert assessments, teacher assessments, and student responses. The study took place in the even semester of the 2024/2025 academic year. The research method used a Research and Development (R&D) approach with stages adapted from the Borg & Gall model which included: preliminary study, planning, initial product development, limited trials, product revision, field trials, operational revisions, operational tests, final revisions, and dissemination and implementation. The results of the study showed that (a) the need for a procedural text learning module was identified through observations, interviews, and questionnaires with teachers and students, which showed the need for innovative teaching tools; (b) the developed module received a